Implementation of Human Rights Principles on the Premeditated Murder: The Case of Banggai Islands - Ismail Ismail; Hamdan Hamdan; Syachdin Syachdin (DE LEGA LATA: JURNAL ILMU HUKUM, 2023)
One of the tasks of the police in the law enforcement process is to investigate and investigate criminal acts. However, this series of police actions is very vulnerable to violations of human rights principles, not least in the case of premeditated murder that occurred in the Banggai Islands. This research is socio-juridical research with a descriptive-qualitative approach. The purpose of this research is to examine the implementation of human rights principles in uncovering premeditated murder by the Banggai Islands Police and to analyze the obstacles in applying human rights principles in investigations. Based on the results of the research, it can be seen that the application of human rights principles in uncovering premeditated murder by the Banggai Islands Police in the investigation has been carried out based on statutory regulations. However, the implementation of human rights principles has not been carried out optimally by police personnel, especially in the juridical rights of suspects. On the other hand, the obstacle to applying human rights principles in the investigation is the low legal awareness. It is recommended that severe intentions are needed to carry out good law enforcement, and it is necessary to improve the moral quality and resources of the Police apparatus